Prevalence and Prognostic Significance of Malnutrition in Hypertensive Patients in a Community Setting - Yang, Zhi-wen; Wei, Xue-biao; Fu, Bing-qi; Chen, Ji-yan; Yu, Dan-qing (Frontiers in Nutrition, 2022)
Background: Malnutrition is a significantly poor prognostic factor for a variety of cardiovascular diseases. However, its prevalence and prognostic value in hypertensive patients is still unclear. The present study sought to determine the prevalence and prognostic value of malnutrition in hypertensive patients in a community setting. Methods: We included 9,949 hypertensive patients from the National Health and Nutrition Examination Survey (2005–2014). The Controlling Nutritional Status (CONUT) score, the Nutritional Risk Index (NRI), and the Naples Prognostic Score (NPS) were applied to assess the nutritional status of participants. A Cox regression model was established to examine the association between malnutrition and cardiovascular and all-cause mortality. Results: In all, 19.9%, 3.9%, and 82.9% hypertensive patients were considered to have malnutrition as evaluated by the CONUT, NRI, and NPS, respectively. Malnutrition assessed by CONUT and NRI was independently associated with cardiovascular mortality (HR [95% CI]) for mild and moderate-to-severe degree of malnutrition, respectively: 1.39 (1.04–1.87) and 3.79 (1.53–9.37) for CONUT; 2.83 (1.57–5.12) and 2.20 (1.204.01) for NRI (all P<0.05), and for all-cause mortality (HR [95% CI]) for mild and moderate-to-severe degree of malnutrition, respectively: 1.51 (1.32–1.72) and 4.25 (2.97–6.10) for CONUT; 1.94 (1.44–2.62) and 2.25 (1.78–2.85) for NRI (all P<0.01). NPS could only independently predict all-cause mortality. Conclusions: Malnutrition was common among hypertensive patients and was closely associated with both long-term cardiovascular and all-cause mortality.